Quality of parental bonding is associated with symptom severity and functioning among individuals at ultra-high risk for psychosis - Peh, Oon Him (2021)
Patients with schizophrenia tend to report having 'affectionless-controlling' mothers when the Parental Bonding Instrument (PBI) is used. However, there is limited research on the parenting styles received by individuals at ultra-high risk (UHR) for psychosis. Furthermore, previous PBI studies have suggested that a three-factor solution is more suitable than the original two-factors. This study aims to i) use a more sensitive measure of parental bonding by conducting an exploratory factor analysis (EFA), and (ii) to explore the association between parental bonding, symptom severity and functioning among the UHR. Data from 164 individuals at UHR and 510 healthy controls were collected. Symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS) and the Calgary Depression Scale for Schizophrenia (CDSS). Functioning was measured using the Global Assessment of Functioning (GAF) and Social and Occupational Functioning Assessment Scale (SOFAS). Confirmatory factor analyses of existing factor structures and EFA of the PBI was conducted. Pearson's correlations and regressions were used to elucidate the associations between parenting factors and assessment scales. EFAs revealed a three-factor solution: 'care', 'authoritarianism', and 'overprotection'. UHR were 1.61 times more likely to report having affectionless-controlling mothers. UHR reported significantly lower maternal and paternal care, and higher maternal and paternal overprotection. Higher paternal overprotection was significantly associated with worse symptoms and functioning. Our findings replicate previous findings among individuals at UHR in an Asian setting, and suggest that affectionless-controlling or affectionless-authoritative-overprotective styles may be a poor fit for individuals at UHR.